Chemically modified bitumens with enhanced rheology and adhesion properties to siliceous aggregates. (15th September 2015) - Cuadri, A.A.; Partal, P.; Ahmad, N.; Grenfell, J.; Airey, G.
Highlights: Evaluation of potential moisture damage in two chemically modified asphalt mixtures. Bitumen modifications by thiourea and an isocyanate/castor oil prepolymer. Both chemical paving binders with improved end-performance. Moisture-induced damage highly influenced by the binder-aggregate adhesion mechanism. Polyurethane modification decreases sensitivity of the asphalt mixture to water. Abstract: Moisture damage is one of the major premature failures that worsens the performance and shortens service life of pavements. This research assesses the effect that two chemical modifiers (thiourea and an isocyanate-functionalized castor oil prepolymer) exerts on the bitumen rheology and on the resistance to potential moisture damage of asphalt mixtures based on siliceous aggregates. Both thiourea and the isocyanate-based prepolymer improve the viscous and viscoelastic behaviours of bitumen at high in-service temperatures, particularly the isocyanate-based reactive modifier. Likewise, the visual inspection of the degree of bitumen coating on loose mixtures exposed to water in a "rolling bottle" test, and further surface free energy measurements, showed that the bitumen modification by the isocyanate-based prepolymer seems to reduce moisture-induced damage on siliceous aggregates. Conversely, thiourea-based modification increases sensitivity of the bitumen–aggregate mixture to water. Different adhesion mechanisms, based on chemical or physical bonds with the aggregate surface, have been proposed for each modifier.